The role of space agencies in the formation of state policy for the development of the space industry - M.O. Psiuk (Економіка, управління та адміністрування)
Taking into account the global trends in the space goods and services market, as well as the strategic importance of the space industry as a multiplier for the development of high-tech innovation economy, it is important to review and optimize the role of space agencies in shaping and prioritizing state space policy. The global space industry is changing rapidly, moving to the fourth stage of development – the construction of the ecosystem of the «New Space», which is characterized by rapid commercialization of the space sector, expanding the range of industry participants and increasing innovation. Today, the domestic space industry needs quick and effective solutions to reform the national space policy, balanced approaches to state regulation and management of the industry, taking into account global trends in the global space sector.